Impact of Flipped Learning Approach on Students Motivation for Learning Digital Electronics Course - Rubina Dutta; Archana Mantri; Gurjinder Singh; Shivani Malhotra; Amit Kumar (National Research Mordova State University, 2020)
Introduction. Various educational institutes follow various approaches to teaching-learning. Compared to the conventional learning approach, a flipped learning/inverted classroom approach was chosen to test students' variability in academic performance and level of motivation through the ARCS model (attention, significance, confidence, satisfaction). Materials and Methods. Keller's Motivation Survey of Instructional Materials was selected to assess the effect (in terms of motivation) of the flipped approach on the students. Keller's ARCS motivation model was the basis for this survey which includes four motivational factors: attention, significance, confidence, and satisfaction. The multiple-choice test was conducted to measure the students' academic performance. Results. After completion of the module, it was noted that significant improvements took place in the students' academic performance, attention, confidence, and level of satisfaction. The relevance factor had not experienced much difference. Results. After completion of the module, it was noted that significant improvements took place in the students' academic performance, attention, confidence, and level of satisfaction. The relevance factor had not experienced much difference. Discussion and Conclusion. The researchers' key goal, according to previous reports, is to integrate various teaching-learning approaches in primary, secondary, k-12, etc.; engineering education has yet to be explored. The research aims to determine the level of academic achievement and motivation of the second year B. E. students for digital electronics course in the flipped learning approach as opposed to conventional teaching approach. The results can be bettered by incorporating parameters such as students' perception, learning attitude, critical thinking skills, etc.